Assessment of house dust trace elements and human exposure in Ankara, Turkey - Gul, Hatice Kubra; Gullu, Gulen; Babaei, Parisa; Nikravan, Afsoun; Kurt-Karakus, Perihan Binnur; Salihoglu, Guray (Springer Heidelberg, 2023)
One of the impacts of the COVID-19 pandemic is leading people remain at homes longer than ever. Considering the elongation of the time people spend indoors, the potential health risks caused by contaminants including heavy metals in indoor environments have become even more critical. The purpose of this study was to evaluate the levels and sources of heavy metals in indoor dust, to assess the exposure to heavy metals via indoor dust, and to estimate the associated health risk. The highest median value was measured for Zn (263 mu g g(-1)), while the lowest median concentration value was observed for Cd (0.348 mu g g(-1)). The levels of elements measured in the current study were found to be within the ranges reported in the other parts of the world, mostly close to the lower end of the range. House characteristics such as proximity to the main street, presence of pets, number of occupants, and age of the building were the house characteristics influencing the observed higher concentrations of certain heavy metals in houses. Enrichment factor values range between 1.79 (Cr) and 20.4 (Zn) with an average EF value of 8.80 +/- 6.80 representing that the targeted elements are enriched (EF>2) in indoor dust in Ankara. Positive matrix factorization results showed that the heavy metals in the house dust in the study area are mainly contributed from sources namely outdoor dust, carpets/furniture, solders, wall paint/coal combustion, and cigarette smoke. Carcinogenic and non-carcinogenic risk values from heavy metals did not exceed the safe limits recommended by EPA. The highest carcinogenic risk level was caused by Cr. The risk through ingestion was higher than inhalation, and the risk levels were higher for children than for adults.
Keywords: Carcinogenic risk; Heavy metals; House dust; Exposure; Risk assessment; Turkey